The informational “cosplay journey” of Star Wars cosplayers in the context of a Facebook group - Emily Vardell; Paul Thomas; Ting Wang (Information Research: An International Electronic Journal)
Introduction. Research on personal information practices has increased in recent decades. Building on this current of thought, the present study explores information practices in the context of serious leisure, looking specifically at the Rey Cosplay Community Facebook group, an online community of Star Wars cosplayers. The work discusses how these fans seek, organize, and share relevant information during the process of making costumes.